Nurseries and „A Drop of Milk” Stations as the Centres Supporting Poor Families in the Kingdom of Poland at the Turn of the XIX-th and XX-th Centuries - Bołdyrew, Aneta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The article is devoted to the centers taking care of children under the age of three which were opened in the second part of the XIX-th century and at the beginning of the XX-th century in the Kingdom of Poland. They were supposed to support the poorest families, especially working or single mothers in fulfilling the educational and protective roles. This purpose was fulfilled mostly by nurseries, „A Drop of Milk” stations and sometimes orphanages. The last ones were for children between 3 and 7 years oldbut sometimes, in the countries, when people worked in the fields, they younger childrencould stay there. The centers for the protection of babies and toddlers were createdand financed by private individuals, charities and other social organizations. Much attentionwas paid by press to the activity of nurseries and „A Drop of Milk” stations inthe form of reports and postulates. The reporters tried to popularize the idea of institutionalprotection of small children, described possible solutions in western Europeancountries, pointed to the fact that such institutions lowered mortality of small childrenfrom the poorest families, especially in the towns. Both theoreticians and practical activity of the institutions concentrated on nursing rather than educational role. In case of nurseries and „A Drop of Milk” stations the cooperation with the children’s mothers was necessary. The mothers were also educated how to protect and bring up a small child.
Keywords: nursery; child care; „A Drop of Milk” station